(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The aim of this paper is to scrutinize various studies on technical and tactical aspects of judo matches. In addition, it also discusses how variables can have practical implications, preceded by a conceptual and historical perspective of the technical and tactical analysis through observation, notation and application of tactical systems of combats. This research deals with important tasks for technical and tactical analysis, such as comparisons of frequency distribution of events over a range of factors such as time structure, number of applied techniques and directions, number of successful actions per minute, quality of attacks awarded with points, movements of elite judo athletes, development and grip forms. This work tries to propose a digest of main studies from 1966 to 2008.